About the certification of railway rails - A. De Iorio; M. Grasso; F. Penta; G.P. Pucillo (Fracture and Structural Integrity)
When the compliance with the European Code of some rail steel has to be verified, the need of carrying out the experimental activities in accordance with several testing Standards forces the operator both to solve the problems related to the choice of a suitable testing practice and often to interpret subjectively Standards guidelines. This does not facilitate the comparability and/or the quality of the results produced by several laboratories. With reference to a series of fatigue, fracture toughness and fatigue crack growth tests carried out by the authors on specimens extracted from rails, the main lacks in the current standards, related to both the choice of the control parameters and the testing procedures, are pointed out. Regarding the crack growth testing, several procedures to compute the crack growth rates to be compared with the limits prescribed by the Code are proposed. These procedures have been applied to a data set produced during the aforementioned testing activity, in order to highlight, by comparison of the results obtained by them, the significant differences in the crack growth rate estimates and the magnitude of the errors that can be done due to the lacks in the standard practices currently adopted.